Embryogenesis protocol for genetic transformation and functional analysis of JERF1 gene in drought-induced Malaysian rice cultivar MR219 - Abiri, Rambod (2018)
In Malaysia, severe drought stresses have affected residents and agricultural crops, especially rice, in various regions of the country and it is likely to continue and may worsen in the future. To mitigate the problems, new tolerant plant varieties to drought must be developed. The main objective of the current research was to develop a suitable in vitro protocol and elucidate the response of Malaysian rice cultivar MR219 to Jasmonate and Ethylene Response Factor 1 (JERF1) gene in drought condition. The best recipe of callogenesis for MR219 was MS media added with 2 mg L-1 of 2,4-D and root was the prominent explant. The best priming conditions were seen at 18 hours of hydropriming and 50 mg L-1 of abscisic acid. For the proliferation phase, the highest efficiency was observed at week four in the MS media supplemented with 2 mg L-1 of 2,4-D, 2 mg L-1 of kinetin, 50 mg L-1 of L-proline, 100 mg L-1 of casein and 30 mg L-1 of silicon. MS media with 3 mg L-1 of KIN, 30 mg L-1 of silicon and 2 mg L-1 of NAA was selected as the best media for regeneration. To promote the roots of the regenerated explants, 0.4 mg L-1 of IBA was found to be the best activator. TRIzol protocol was found to be an appropriate method for isolating high quality RNA from the tomato leaves and fruits. Four hours of NaCl and ABA treatments on the tomato prior to the nucleic acids extractions produced the highest JERF1 expression and led to the successfully isolating the JERF1 gene. The entry and the expression vectors were constructed using Gateway® Technology. Agrobacterium-mediated transformation method was used to transform JERF1 gene to MR219. Transgenicity of the transformed plants was evaluated using polymerase chain reaction, q-PCR and High-Performance Liquid Chromatography. The result of functional study has shown that the average width of the wild type seeds was significantly higher than transgenic seeds. Meanwhile, the seeds ratio of wild type was higher in comparison to transgenic in the second generation. The morpho- and physiological results of the two-week-old rice seedlings had shown that the responses of both wild type and transgenic rice in terms of shoot and root length and plumule fresh and dry weight were significantly different (p≤0.01). The responses of both wild type and transgenic rice in terms of the shoot and root length, leaf proline, root proline, chlorophyll a and b, total chlorophyll and carotenoid and other pigments were significantly different (p≤0.01) in three-week-old rice. These results have confirmed the significant differences (p≤0.05) between wild type and transgenic plants in terms of the ratio of root to shoot proline in three-week-old rice. The concentrations of some amino acids such as aspartic acid, serine, glycine, proline and cysteine were significantly different between wild type and transgenic plants. Real-time PCR confirmed the over-expression of OsLTP1, OsCDPK13, OsP5CS and OsSPDS2 by JERF1 genes in transgenic plants. To conclude, the results of this experiment confirmed the high efficiently of somatic embryogenesis protocol and potential of JERF1 as a prominent gene under drought stress condition.